Effect of multidisciplinary team care on the risk of recurrence in breast cancer patients: A national matched cohort study - Tsai, Chang-Hung (Breast, 2020)
BACKGROUND: Cancer has been the leading cause of death in the past decade in Taiwan, with breast cancer being the most common type of cancer in females. Very few studies looked at the risk of recurrence in patients who received multidisciplinary team (MDT) care. We analyzed the influence of MDT on the risk of recurrence and death in breast cancer patients. METHOD: In this retrospective study, we included newly diagnosed patients from 2004 to 2010. The study included 9,266 breast cancer patients who were enrolled in MDT care and 9,266 patients who were not. The study used log-rank test to analyze patients’ characteristics, hospital characteristics, cancer staging, and treatment methods to compare the recurrence rates in MDT care and non-MDT care participants. We used Cox proportional hazards model to examine the effect of MDT and associated factors on the risk of recurrence and mortality of breast cancer patients. RESULTS: Relative risk of recurrence was lower for patients who received MDT care than for patients who did not (HR, 0.84; 95%CI: 0.70–0.99) after matching. The mortality risk for breast cancer patients with relapse was 8.48 times (95%CI: 7.53–9.54) than that for patients without relapse. CONCLUSIONS: The relative risk of recurrence and death was significantly lower for breast cancer patients who received MDT care than for those who did not. We suggest that MDT care be implanted in the National Health Policy settings of breast cancer patients.